Clinical Features of iatrogenic Pharyngo-esophageal perforation in very low birth weight infants - Shu Eguchi; Yoshiya Hisaeda; Toshiko Ukawa; Mayu Koto; Miku Hosokawa; Chisa Tsurisawa; Tomohiro Takeda; Shusuke Amagata; Atsushi Nakao (Pediatrics and Neonatology)
Background: Iatrogenic pharyngoesophageal perforation (IPEP) is one of the complications of gastric tube insertion and it tends to occur more frequently in premature infants. Although the frequency is significantly low, attention should be paid as it can lead to serious outcomes with high mortality. This study will help raise awareness with respect to early diagnosis, management, and prevention. Methods: We performed a retrospective cohort study of all very low birth weight infants diagnosed with IPEP between 1993 and 2022. Results: A total of 6 patients (0.27% of very low birth weight infants) with the diagnosis of IPEP were included. The median gestational age was 27 + 1 weeks (range 23+5–28 + 6 weeks), and the median birth weight was 823 g (range 630–1232 g). Symptoms included difficulty with gastric tube insertion, bloody secretions in the oral cavity, and increased oral secretions. X-rays revealed aberrant running of the gastric tube in all patients. In three cases, contrast studies demonstrated contrasted mediastinum tapering like a bead. Laryngoscope was used to view the perforation sites but this was not useful in the smallest patient. All patients were treated conservatively with antibiotics and survived. Conclusions: When inserting a gastric tube for premature infants, it is critical to remember that these infants are at risk of IPEP. In addition to a frontal X-ray, a lateral X-ray and contrast study may be useful for early diagnosis.